1995
DOI: 10.1007/bf01409712
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of an interactive, session-oriented computerized Negotiation Support System (NSS)

Abstract: Abstract.Negotiating is one of the four major decisional roles played by managers. In fact, resolving conflict is said to occupy 20% of a manager's working hours. This growing frequency of negotiation scenarios coupled with the increasing complexity of the issues which need to be resolved in a negotiation make the possibility of computer enhancement for negotiation very appealing. Implementations of computerized Negotiation Support Systenls (NSS) in the business world, international affairs, labor law, and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Consistently, Oliver et al (1994) found that the difference between negotiators expectations and outcomes is significantly correlated with negotiator satisfaction. In Foroughi et al (1995) experiment, it showed that NSS supported dyads achieved greater satisfaction than Non-NSS dyads. NSS dyads reported greater satisfaction than the DSS only and Non-NSS dyads in Delaney et al (1997) study.…”
Section: Satisfaction In Nss Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistently, Oliver et al (1994) found that the difference between negotiators expectations and outcomes is significantly correlated with negotiator satisfaction. In Foroughi et al (1995) experiment, it showed that NSS supported dyads achieved greater satisfaction than Non-NSS dyads. NSS dyads reported greater satisfaction than the DSS only and Non-NSS dyads in Delaney et al (1997) study.…”
Section: Satisfaction In Nss Researchmentioning
confidence: 92%
“…In addition to the complexity of negotiation itself, to identify and achieve optimal outcomes may also be hindered by negotiators' limited information processing capacity and capability, cognitive biases, and socio-emotional obstacles (Bazerman et al 1985;Foroughi et al 1995). The challenges of negotiation and the cognitive limitations of human negotiators have led researchers to pursue computer support in the form of NSS (Goh et al 2000).…”
Section: Background Review Of Negotiation Support Systemsmentioning
confidence: 97%
“…If such situations are examined carefully, it can be seen that their complexity lies mainly in the difficulty of identifying exact or close matches between counter-party needs and objectives, in the discrimination of preferences, and, finally, in making choices among alternatives (Foroughi et al, 1995). Furthermore, the overall underlying European Journal of Operational Research 145 (2003) [232][233][234][235][236][237][238] www.elsevier.com/locate/dsw business goals require the simultaneous consideration of a variety of issues, thus making negotiations more complex or even impossible (Jarke et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of economic (in)equity of the exchanged offers is captured by the difference in payoffs between the two negotiators, referred to as contract balance (Foroughi et al 1995). It reflects the degree to which an offer is disproportionately more advantageous to one side and the degree to which negotiators claim value for themselves compared to what they offer to the counterpart.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…As discussed above, the contract balance is defined as the difference between the utility scores of the two negotiators and has been widely used as an economic measure of (in)equity in negotiation research (Foroughi et al 1995). An outcome is Pareto efficient when no alternative agreement is available leaving one negotiator better off while not making the other negotiator worse off.…”
Section: Utility Elicitation and Economic Measuresmentioning
confidence: 99%